Associations between reading and writing postures and myopia among school students in Ningbo, China - Jiang, Danjie; Shi, Bijun; Gao, Hua; Guo, Yanbo; Zhou, Shaoying; Zhang, Yan (Frontiers in Public Health, 2022)
Background We conducted this study to investigate the prevalence of myopia among school students in Ningbo and to explore the associations between reading and writing postures and myopia. Methods A population-based and cross-sectional study was conducted, and 3,256 school students aged 8–19 years were recruited. Each enrolled subject was assessed for uncorrected distance visual acuity (UDVA) using a standard logarithmic visual acuity E-chart and a non-cycloplegic autorefraction examination. Self-administered questionnaires were used to investigate myopia-related reading and writing postures and behavioral habits among school students. Results The prevalence of myopia among primary school, middle school, and high school students was 61.49, 81.43, and 89.72%, respectively. Regarding the associations between reading and writing postures and myopia, we identified that a reading distance >33 cm is a protective factor for myopia in female students [odds ratio (OR) = 0.31, 95% confidence interval (CI) = 0.15–0.64], in both primary school (OR = 0.55, 95% CI = 0.30–0.99) and middle school (OR = 0.37, 95% CI = 0.15–0.90). Conclusions A reading distance >33 cm can be used as an additional measure to prevent and control myopia. Proper postural measures for reading and writing may have educational and public health benefits.